Investigating leverage effect on Turkish stock market with ARCH models within two sub-groups - Demir, Ibrahim; Cene, Erhan (ISTANBUL UNIV, 2012)
Predicting the stock market movements have always been a very interesting subject to study. The most important concept that is related with stock market movements is volatility which is a measure of mobility at the market. In this study, by using IMKB indexes closing values at the period of 04.11.2002 - 25.11.2011, two sub-periods are defined and with the help of different ARCH models, it is tried to find any structural differences between these sub-periods with the help of leverage effect.
Keywords: Volatility; ARCH; Leverage Effect; Business & Economics